Cognição e aprendizagem de crianças com deficiência intelectual: evidências sobre o funcionamento cognitivo - Silva, Maria Simone da (2019)
This research is interested in the relationship between cognition and learning of students with intellectual disabilities (ID), as it seeks to analyze the cognitive functions / mechanisms employed by these children, specifically, in didactic-pedagogical activities of written language, in the classroom context. class. Our interest is to know in more depth also the relationship between the cognitive functions of these subjects with ID and the pedagogical mediations that can collaborate in support of their learning process when in common classroom situations / activities. Methodologically, we seek to accompany them in the manifestations in use of their cognitive functions and to analyze aspects such as attention / perception, memory, motivation, as well as the ability to transfer, generalization, synthesis and metacognition. These aspects are presented by the literature by Figueiredo (2008, 2010, 2013 2018) and Feuerstein (2016), as directly implicated in school learning and marked as extremely weak elements in these subjects. The approach is the qualitative research, notably, the monitoring of the processes involved in the act of learning of the knowing subjects. The focus subjects of the study are two students with ID, from a 2nd year class, therefore, focusing on literacy work, from a municipal school in Fortaleza, District V. The methodology will consist of three steps: i. Diagnostic assessment of children's level (psychogenetic assessment) and Case Study composition of these subjects; ii. Construction of didactic activities (together with the teacher), to be developed in the classroom to the students (10 sessions); iii. Systematic monitoring of students with ID included in classrooms regarding the learning process and manifestation of mental functions during the proposed activities. Our expectation is that studies of this investigative nature tend to contribute to identify how children with IDD learn and thus be able to mobilize mediations and pedagogical strategies that may favor the learning of these students and, simultaneously, may compose the formative knowledge for teaching.